Time-dependent trends in cardiovascular adverse events during follow-up after carotid or iliofemoral endarterectomy. Issue 11 (26th June 2017) - van Koeverden, I D; van Haelst, S T W; Haitjema, S; de Vries, J-P P M; Moll, F L; den Ruijter, H M; Hoefer, I E; Dalmeijer, G W; de Borst, G J; Pasterkamp, G
Abstract: Background: Recent observations have suggested a decline in vulnerable carotid artery and iliofemoral atherosclerotic plaque characteristics over the past decade. The aim of this study was to determine whether, in the presence of clinically manifest carotid or peripheral artery disease, secondary adverse cardiovascular events decreased over this period. Methods: Patients included in the Athero-Express biobank between 2003 and 2012 were analysed. During 3-year follow-up, composite cardiovascular endpoints were documented yearly, including: myocardial infarction, coronary interventions, stroke, peripheral interventions and cardiovascular death. The major cardiovascular endpoint consisted of myocardial infarction, stroke and cardiovascular death. Results: Some 1684 patients who underwent carotid endarterectomy (CEA) and another 530 who had iliofemoral endarterectomy (IFE) were analysed. In total, 405 (25·2 per cent) and 236 (45·9 per cent) patients had a composite cardiovascular endpoint within 3 years after CEA and IFE respectively. Corrected for possible confounders, the percentage of patients with a secondary cardiovascular event after CEA did not change over time (hazard ratio (HR) 0·91, 95 per cent c.i. 0·65 to 1·28; P = 0·590, for 2011–2012 versus 2003–2004). In patients who had IFE, the incidence of secondary cardiovascular events significantly decreased only in the last 2 years (HR 0·62, 0·41 to 0·94; P = 0·024), owing to a decrease in peripheral (re)interventions in 2011–2012 (HR 0·59, 0·37 to 0·94; P = 0·028). No decrease in major cardiovascular events was observed in either group. Conclusion: In patients who had undergone either CEA or IFE there was no evidence of a decrease in all secondary cardiovascular events. There were no differences in major cardiovascular events. Abstract : No decline in events